Improvement in material removal rate (MRR) using magnetic field in TW-ECSM process. Issue 1 (2nd January 2017) - Rattan, Nav; Mulik, Rahul S.
ABSTRACT: Electro chemical spark machining (ECSM) has the ability to machine electrically nonconducting materials successfully and economically. It has been seen that electrolyte circulation hindered in the close vicinity of the machining zone during the machining process, which leads to the reduction in material removal rate (MRR). In the present research, a magnetohydrodynamic (MHD) convection approach is discussed, which increases the electrolyte flow used in the travelling wire (TW)-ECSM process. The existence of magnetic field in the electrolysis process induces the Lorentz forces, which are responsible for MHD convection in the process. The experimental results showed that the MHD convection pushes the electrolyte to improve the movement of the electrolyte in the sparking zone to improve MRR in the TW-ECSM process. The experimental results revealed that the MRR increased in the presence of a magnetic field as compared to machining under no magnetic field, with the improvement factor ranging from 9.09% to 200% under different processing conditions. The discharge current was also reduced by the application of magnetic field in the machining process.